2014
DOI: 10.1039/c4ob00005f
|View full text |Cite
|
Sign up to set email alerts
|

A unique dithiocarbamate chemistry during design & synthesis of novel sperm-immobilizing agents

Abstract: 1-Substituted piperazinecarbodithioates were obtained by an unusual removal of CS2 in benzyl substituted dithiocarbamate derivatives under acid and basic conditions during design and synthesis of 1,4-(disubstituted)piperazinedicarbodithioates as double edged spermicides. A plausible mechanism for CS2 removal has been proposed. All synthesized compounds were subjected to spermicidal, antitrichomonal and antifungal activities. Twenty-one compounds irreversibly immobilized 100% sperm (MEC, 0.06-31.6 mM) while sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
(138 reference statements)
0
6
0
Order By: Relevance
“…These observations suggest that not only the protein sulfhydryl groups can be oxidized by Stattic V, but an irreversible modification of sulfhydryl groups, through alkylation, can also occur which would explain the lower level of reduced thiols reported here. This mechanism, alkylation of free thiols, has been suggested to explain the action of some spermicidal agents that causes sperm immobilization (Jangir et al ., ; Pandey et al ., ). In fact, in our incubation conditions, iodoacetamide effectively immobilized spermatozoa, an effect that was prevented by NAC or D‐Pen but not by DTT (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that not only the protein sulfhydryl groups can be oxidized by Stattic V, but an irreversible modification of sulfhydryl groups, through alkylation, can also occur which would explain the lower level of reduced thiols reported here. This mechanism, alkylation of free thiols, has been suggested to explain the action of some spermicidal agents that causes sperm immobilization (Jangir et al ., ; Pandey et al ., ). In fact, in our incubation conditions, iodoacetamide effectively immobilized spermatozoa, an effect that was prevented by NAC or D‐Pen but not by DTT (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic energy metabolism, spermatozoa motility, and defense against reactive oxygen species, which are essential to the survival of both sperm and anaerobic microbes, such as Trichomonas vaginalis in the host, depending on the availability of free thiols. Thus, sulfhydryl binding agents (oxidants) are an option for the design of dual-purpose sperm immobilizing agents [112,113]. These agents interact with accessible thiols on sperm and T. vaginalis, resulting in lipid peroxidation, insufficient axonemal phosphorylations, and, consequently, loss of motility and viability.…”
Section: Sulfhydryl Binding Agentsmentioning
confidence: 99%
“…22,23 The isolated amide salt 4 was then cyclised in acetonitrile (CH3CN) at reflux for 72 h, giving the desired product in a better yield in comparison to a one-step synthesis method performed in parallel, in which intermediate amid salt 4 was the major product, with the desired compound obtained in a very low yield (6 %). 24 Benzyl piperazine derivatives (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) were obtained in good yields by reacting the corresponding commercially available benzyl chloride (7-21) with a large excess of piperazine (6), in order to avoid a double nucleophilic attack and the formation of a disubstituted piperazine molecule. 25,26,27 Piperazine derivatives (34)(35)(36), in which the methylene linker has been replaced, were prepared exploiting different reagents and conditions in order to obtain the desired product in a good yield after column chromatography purification.…”
Section: Chemistrymentioning
confidence: 99%
“…Final compounds 47-53 were obtained following a different two-step reaction, in which piperazine derivatives 31-37 and a large excess of carbon disulfide were reacted for 2 h in a strong basic ethanolic solution of potassium hydroxide (KOH), forming dithiocarbamate salts 31a-37a. 31,32 The salts, recovered by filtration, were then reacted with 5 for 24 h using methanol (MeOH) as solvent and triethylamine (Et3N) as base, to afford the final products 47-53. Although both methods produced a similar range of final yields, the use of EtOH or MeOH as solvent instead of DMF and the absence of formation of side products, which makes the reaction purification much easier, suggested that the 2-step reaction was the most efficient procedure to follow.…”
Section: Chemistrymentioning
confidence: 99%